The Pengembangan Tujuan dalam Ilmu Pendidikan Islam Korelasinya dengan Perubahan Zaman - Hoerotunnisa Hoerotunnisa; Ratu Suntiah; Mursidin Mursidin; Miftah Falah Udwi Syarfiah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study is to examine how Islamic educational goals have evolved and how they relate to the times. This study employs descriptive qualitative methodologies and includes direct observation and in-depth interviews in a number of Islamic educational establishments, such as schools and Islamic boarding schools. Teachers, school administrators, and students from different backgrounds make up the research subjects. The survey's conclusions demonstrate how the objectives of Islamic education have changed, now include not just the study of religious science but also the cultivation of character, life skills, and critical thinking abilities. But there are a number of obstacles in the way of achieving this objective, such as divergent interpretations of Islamic teachings, the impact of globalization, and a lack of public support. The study suggests that in order to address these issues, more comprehensive curricular revisions, teacher training, and enhanced community-education cooperation are required. It is anticipated that this study will offer insightful information for the creation of contemporary, pertinent, and sustainable Islamic education.